Makna Kesehatan Mental Dalam Film Bolehkah Sekali Saja Ku Menangis Analisis Semiotika Roland Barthers - Syahla Hidayah; Fakhrur Rozi (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the representation of mental health in the film Bolehkah Sekali Saja Ku Menangis using Roland Barthes' semiotic approach. The problem raised is how denotative, connotative, and mythical meanings in the film form a narrative about psychological disorders and the dynamics of character emotions. The film features the main character, Tari, who experiences psychological stress due to family conflict and tries to recover through discussion groups. This study uses a qualitative approach with a case study method. Data collection techniques are carried out through observation and documentation, with analysis focused on ten main scenes in the film. The results of the study show that mental health issues are represented through visual and verbal symbols such as dark rooms, mirrors, silent expressions, and emotional dialogues. The film dismantles social myths about emotional strength, intergenerational trauma, and the role of patriarchal families in forming inner wounds. These representations form a new narrative that is more inclusive and empathetic to mental health issues. Thus, this film is not only artistic but also educational, and contributes as an alternative media in the literacy campaign and reducing the stigma against mental health in Indonesia.